Answer:
Step-by-step explanation:
m₁ = 3.4 kg m₂ = 6.8 kg
u₁ = 5.7 m/s u₂ = 3.8 m/s
after collision
v₂ = 4.8 m/s
now,
m₁ u₁ + m₂ u₂ = m₁ v₁ + m₂ v₂
3.4 × 5.7 + 6.8 × 3.8 = 3.4 × v₁+ 6.82 × 4.8
v₁ = 3.67 m/s
a) velocity of 3.4 kg block = 3.67 m/s
b) total change in kinetic energy=
![\Delta KE = ({(1)/(2)mv^2_1 +(1)/(2)mv^2_2 }) -((1)/(2)mu^2_1 +(1)/(2)mu^2_2 )\\\Delta KE = ({(1)/(2)*3.4* 3.67^2 +(1)/(2)* 6.8* 4.8^2 }) -({(1)/(2)*3.4* 5.7^2 +(1)/(2)* 6.8* 3.8^2 } )\\\Delta KE =-3.09J](https://img.qammunity.org/2020/formulas/physics/high-school/wef6deow6w6414pgquc82olg3iv1eh74qt.png)
hence, K E comes out to be -3.09J.
c)
m₁ u₁ + m₂ u₂ = m₁ v₁ + m₂ v₂
3.4 × 5.7 + 6.8 × 3.8 = 3.4 × v₁+ 6.82 × 7.6
v₁ = - 1.94 m/s
change in K E
![\Delta KE = ({(1)/(2)mv^2_1 +(1)/(2)mv^2_2 }) -((1)/(2)mu^2_1 +(1)/(2)mu^2_2 )\\\Delta KE = ({(1)/(2)*3.4* (-1.94)^2 +(1)/(2)* 6.8* 4.8^2 }) -({(1)/(2)*3.4* 5.7^2 +(1)/(2)* 6.8* 3.8^2 } )\\\Delta KE = -19.59J](https://img.qammunity.org/2020/formulas/physics/high-school/cmzgmse3m840iwq26mi8rpu424sgncxa4u.png)
hence the change is kinetic energy comes out to be -19.59J